2016
DOI: 10.1007/s12105-016-0718-5
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme Expression Can be Useful to Distinguish Mammary Analog Secretory Carcinoma from Acinic Cell Carcinoma of Salivary Glands

Abstract: Lysozyme is an enzymatic marker of acinar and intercalated duct cells of normal salivary glands. The aim of this study was to verify whether lysozyme expression could be useful to distinguish acinic cell carcinoma (ACC) from its main mimic, mammary analog secretory carcinoma (MASC). For comparison, DOG1 expression was analyzed as well. Seventeen cases of ACC, 15 MASC, and 125 other salivary tumors were studied. Lysozyme expression was found in tumor cells as well as in secreted material of MASC (86.6 % of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Chen et al demonstrated that PRC1 could promote early recurrence of patients with hepatocellular carcinoma by regulating the expression of FANCI (43). Mariano FV et al demonstrated that the expression of LYZ could be used to differentiate mammary analog secretory carcinoma from acinic cell carcinoma of salivary glands (44). Wu et al demonstrated that the expression of HMGN5 was increased in bladder cancer cells and high expression of HMGN5 was associated with poor prognosis of patients with bladder cancer (45).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al demonstrated that PRC1 could promote early recurrence of patients with hepatocellular carcinoma by regulating the expression of FANCI (43). Mariano FV et al demonstrated that the expression of LYZ could be used to differentiate mammary analog secretory carcinoma from acinic cell carcinoma of salivary glands (44). Wu et al demonstrated that the expression of HMGN5 was increased in bladder cancer cells and high expression of HMGN5 was associated with poor prognosis of patients with bladder cancer (45).…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis includes acinic cell carcinoma, mucoepidermoid carcinoma, and adenocarcinoma (primary or metastatic); the majority of cases can be resolved by immunohistochemistry and ETV6 FISH on cell block material. As discussed above, canalicular staining for DOG1 is a feature of acinic cell carcinoma and negative or nonspecific cytoplasmic staining may occur in secretory carcinoma . Acinic cell carcinoma typically is negative for S100 and mammaglobin, although focal staining for either marker may be observed .…”
Section: Introductionmentioning
confidence: 95%
“…48,49 In contrast, its most frequent mimic, secretory carcinoma, often demonstrates mammaglobin and S100 staining, and usually is DOG1 negative (or may demonstrate nonspecific cytoplasmic staining). 47,[50][51][52][53] Some authors also have reported that carbonic anhydrase VI positivity can distinguish acinic cell carcinoma from secretory carcinoma. 54 Acinic cell carcinoma also is negative for p63, which helps distinguish it from mucoepidermoid carcinoma.…”
Section: Acinic Cell Carcinomamentioning
confidence: 99%
See 2 more Smart Citations